Fiber woven structure dielectric film for high-energy-storage-density capacitor and preparation method of fiber woven structure dielectric film
Polyetherimide/polyvinylidene fluoride-hexafluoropropylene fibers with core-shell structures were prepared by coaxial electrospinning technology, and composite films were formed by stacking hot pressing, which solved the problem of difficult to balance between dielectric constant and breakdown strength of existing materials, and achieved composite films with high energy storage density and high mechanical properties.
Patent Information
- Application Number
- CN202411894540.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2044-12-20
AI Technical Summary
It is difficult to balance the existing polymer-based dielectric materials between increasing the dielectric constant and breakdown strength, resulting in the energy storage density not meeting the needs of high-power density energy storage capacitors.
Polyetherimide/polyvinylidene fluoride-hexafluoropropylene core-shell structure fibers with core-shell structures were prepared by coaxial electrospinning technology, and a composite film was formed by stacking hot pressing, and the fiber composition content, orientation and stacking direction were adjusted to enhance the mechanical strength and dielectric properties of the film.
The breakdown strength and energy storage density of the composite film are significantly improved, and the high dielectric constant and high mechanical performance are achieved, meeting the needs of high power density energy storage capacitors.
Smart Images

Figure CN119872028A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of polymer dielectric materials used in electrostatic capacitors, and in particular relates to a dielectric film for capacitors with high breakdown strength and high energy storage density and a preparation method thereof. Background Art
[0002] Dielectric film capacitors have ultrafast charging and discharging speeds and extremely high power density. As a basic component of modern electronic and power systems, they are widely used in hybrid vehicles, power transmission and electromagnetic weapons, and are an important energy storage device. However, the energy storage capacity of dielectric capacitors is much lower than that of electrochemical energy storage devices. The dielectric constant of currently commercially available dielectric materials is relatively low (generally lower than 2.2), which cannot meet the urgent needs of compact, reliable and efficient capacitors. Polyvinylidene fluoride-hexafluoropropylene is a ferroelectric polymer dielectric material with a relatively high dielectric constant (8 to 12), but this type of polymer has high polarization loss and insufficient breakdown electric field resistance. Polyetherimide is a type of linear polymer dielectric material with very low polarization loss, but its dielectric constant (~3.2) is slightly lower than that of ferroelectric polymers. Therefore, how to improve the breakdown strength of dielectric film materials as capacitor energy storage media while maintaining a high dielectric constant is a key issue in achieving high energy storage density. Summary of the invention
[0003] The present invention aims at the difficulty of simultaneously improving the dielectric constant and breakdown strength of polymer-based dielectric materials, resulting in the energy storage density being unable to meet the needs of high-power density energy storage capacitors. The core-shell structured polyetherimide / polyvinylidene fluoride-hexafluoropropylene core-shell structured fibers are prepared by coaxial electrospinning technology, and laminated and hot-pressed to form a composite film. The woven structure is regulated by adjusting the composition and content of the core-shell fibers, the fiber orientation stacking direction, and the number of stacked layers to enhance the mechanical strength of the film, form deep traps to capture carriers, significantly improve the breakdown strength, and utilize interface polarization to maintain a high dielectric constant, thereby comprehensively improving the energy density. Specifically:
[0004] 1. Greatly improve the breakdown strength of polyetherimide / polyvinylidene fluoride-hexafluoropropylene composite film dielectric;
[0005] 2. Improve the mechanical and dielectric properties of the composite film to obtain energy storage dielectric materials with both high energy storage density and high charge and discharge efficiency.
[0006] The technical solution adopted by the present invention is:
[0007] The polyetherimide / polyvinylidene fluoride-hexafluoropropylene composite film with a certain three-dimensional cross-woven structure was prepared by electrospinning and hot pressing. The detailed steps are as follows:
[0008] Step 1: Weigh a certain mass of polyvinylidene fluoride-hexafluoropropylene powder and place it in a beaker, add N-methylpyrrolidone solvent and acetone in a volume ratio of 1:1 into the beaker, and stir at room temperature to obtain an outer layer precursor solution. A series of outer layer precursor solutions with different volume fractions can be obtained by adjusting the mass of polyvinylidene fluoride-hexafluoropropylene powder.
[0009] Step 2: Weigh a certain mass of polyetherimide particles and place them in a beaker, add N-methylpyrrolidone solvent and acetone in a volume ratio of 9:8 into the beaker, and stir at 40° C. to obtain an inner layer precursor solution. A series of inner layer precursor solutions with different volume fractions can be obtained by adjusting the mass of the polyetherimide particles.
[0010] Step 3: Use two 10mL syringes to absorb the inner and outer layer precursor solutions respectively, connect the two syringes to the two interfaces of the special coaxial spinning needle respectively, apply a high voltage of 16-18kV to carry out the electrospinning process, and the speed of the spinning receiving shaft is 600 (±50) rpm. The propulsion speed ratio of the inner and outer layer solutions is consistent with the ratio of the inner and outer layer areas of the coaxial spinning needle. The product of the ratio of the volume concentration of polyetherimide in the inner layer precursor solution to the volume concentration of polyvinylidene fluoride-hexafluoropropylene in the outer layer precursor solution and the ratio of the inner and outer layer areas of the coaxial spinning needle is the volume ratio of the two components of polyetherimide and polyvinylidene fluoride-hexafluoropropylene in the obtained spun fiber, that is,
[0011]
[0012] During the entire electrospinning process, the ambient temperature was maintained at about 26°C, the humidity was between 10% RH and 30% RH, and the spinning time was 12h to 18h.
[0013] Step 4: Remove the prepared fiber felt from the aluminum foil, first dry it in air at 120°C for 2 hours to remove excess solvent, and then dry it in vacuum for more than 24 hours.
[0014] Step 5: Stack 2 to 3 layers of fiber mat in the same direction or in a cross-vertical direction and place them in the mold. First, set the heating table of the hot press to 190℃ and preheat for 30 minutes. Put the stacked fiber mat in and keep it at 5MPa for 10 minutes, then release the pressure for 5 minutes to expel the air. Then pressurize at 200℃ and 210℃ for 10 minutes and then release the pressure for 5 minutes. Finally, apply a pressure of 7.5MPa at 220℃ for 1 hour, and blow and cool to obtain composite films with different structures.
[0015] The advantages and beneficial effects of the present invention are:
[0016] 1. The breakdown strength of the three-dimensional cross-woven structure of polyetherimide / polyvinylidene fluoride-hexafluoropropylene composite film can reach 737.5kV / mm, which is nearly 50kV / mm higher than that of the polyetherimide / polyvinylidene fluoride-hexafluoropropylene composite film in a single fiber direction.
[0017] 2. The composite film exhibits excellent dielectric properties, and the energy storage density can reach 29.3J / cm 3 , which is 1.5 times that of the composite film with a single fiber direction, and the charging and discharging efficiency can reach more than 70%. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 It is a flow chart made by the present invention.
[0019] Figure 2 This is a vertical cross-sectional image of a three-dimensional woven structure composite film.
[0020] Figure 3 The invention discloses the breakdown voltage Weibull distribution and characteristic breakdown strength of a three-dimensional woven structure composite film with a polyetherimide volume fraction of 10%.
[0021] Figure 4 It is the discharge energy density of the three-dimensional woven structure composite film with a volume fraction of 10% of polyetherimide under different electric fields.
[0022] Figure 5 It is the charge and discharge efficiency of the three-dimensional woven structure composite film with a volume fraction of 10% of polyetherimide under different electric fields.
[0023] Figure 6 It is a comparison of the highest breakdown strength and highest energy storage density of composite films with three different fiber structures. DETAILED DESCRIPTION
[0024] In order to better clarify the technical solution of the present invention, Figure 1-6 , and is explained with specific examples, as detailed below:
[0025] Implementation case 1:
[0026] (1) Weigh 3.6 g of polyvinylidene fluoride-hexafluoropropylene powder and place it in a 50 mL beaker. Add 8 mL of N-methylpyrrolidone solvent and 8 mL of acetone to the beaker and stir at room temperature for 24 h to obtain an outer layer precursor solution.
[0027] (2) Weigh 1.8 g of polyetherimide particles and place them in a 50 mL beaker. Add 9 mL of N-methylpyrrolidone solvent and 8 mL of acetone into the beaker and stir at 40 °C for 12 h to obtain an inner layer precursor solution.
[0028] (3) Use two 10mL syringes to absorb the inner and outer layer precursor solutions respectively, connect the two syringes to the two interfaces of the 23G / 17G coaxial spinning needle respectively, apply a high voltage of 18kV for the electrospinning process, the speed of the spinning receiving shaft is 600 rpm, the propulsion speeds of the inner and outer layer solutions are 0.5 μL / min and 6 μL / min respectively, the ambient temperature of the entire electrospinning process is maintained at 26°C, the humidity is less than 30% RH, and the spinning time is 18h.
[0029] (4) The prepared fiber felt was removed from the aluminum foil, first dried in air at 120°C for 2 h to remove excess solvent, and then dried in a vacuum for 24 h.
[0030] (5) Stack two layers of fiber mat in the same direction and place them in a mold. First, set the heating table of the hot press to 190°C for preheating for 30 minutes. Place the stacked fiber mat in the mold and keep it at 5 MPa for 10 minutes, then release the pressure for 5 minutes to expel the air. Then, pressurize at 200°C and 210°C for 10 minutes and then release the pressure for 5 minutes. Finally, apply a pressure of 7.5 MPa at 220°C for 1 hour, and after cooling with air, obtain a single-direction structure composite film with a polyetherimide volume fraction of 5%.
[0031] Implementation case 2:
[0032] (1) Weigh 3.6 g of polyvinylidene fluoride-hexafluoropropylene powder and place it in a 50 mL beaker. Add 8 mL of N-methylpyrrolidone solvent and 8 mL of acetone to the beaker and stir at room temperature for 24 h to obtain an outer layer precursor solution.
[0033] (2) Weigh 1.8 g of polyetherimide particles and place them in a 50 mL beaker. Add 9 mL of N-methylpyrrolidone solvent and 8 mL of acetone into the beaker and stir at 40 °C for 12 h to obtain an inner layer precursor solution.
[0034] (3) Use two 10mL syringes to absorb the inner and outer layer precursor solutions respectively, connect the two syringes to the two interfaces of the 23G / 17G coaxial spinning needle respectively, apply a high voltage of 18kV for the electrospinning process, the speed of the spinning receiving shaft is 610 rpm, the propulsion speeds of the inner and outer layer solutions are 0.5 μL / min and 6 μL / min respectively, the ambient temperature of the entire electrospinning process is maintained at 26°C, the humidity is less than 30% RH, and the spinning time is 18h.
[0035] (4) The prepared fiber felt was removed from the aluminum foil, first dried in air at 120°C for 2 h to remove excess solvent, and then dried in a vacuum for 24 h.
[0036] (5) Stack two layers of fiber mat in a cross-vertical direction and place them in a mold. First, set the heating table of the hot press to 190°C for preheating for 30 minutes. Place the stacked fiber mat in the mold and keep it at 5MPa for 10 minutes, then release the pressure for 5 minutes to expel the air. Then, pressurize at 200°C and 210°C for 10 minutes and then release the pressure for 5 minutes. Finally, apply a pressure of 7.5MPa at 220°C for 1 hour, and after cooling with air, obtain a double-layer cross-structure composite film with a polyetherimide volume fraction of 5%.
[0037] Implementation case three:
[0038] (1) Weigh 3.6 g of polyvinylidene fluoride-hexafluoropropylene powder and place it in a 50 mL beaker. Add 8 mL of N-methylpyrrolidone solvent and 8 mL of acetone to the beaker and stir at room temperature for 24 h to obtain an outer layer precursor solution.
[0039] (2) Weigh 1.8 g of polyetherimide particles and place them in a 50 mL beaker. Add 9 mL of N-methylpyrrolidone solvent and 8 mL of acetone into the beaker and stir at 40 °C for 12 h to obtain an inner layer precursor solution.
[0040] (3) Use two 10mL syringes to absorb the inner and outer layer precursor solutions respectively, connect the two syringes to the two interfaces of the 23G / 17G coaxial spinning needle respectively, apply a high voltage of 17.5kV to carry out the electrospinning process, the speed of the spinning receiving shaft is 550 rpm, the propulsion speeds of the inner and outer layer solutions are 0.5 μL / min and 6 μL / min respectively, the ambient temperature of the entire electrospinning process is maintained at 26°C, the humidity is lower than 20% RH, and the spinning time is 15h.
[0041] (4) The prepared fiber felt was removed from the aluminum foil, first dried in air at 120°C for 2 h to remove excess solvent, and then dried in a vacuum for 24 h.
[0042] (5) The fiber felts were stacked in three layers in a cross-vertical direction and placed in a mold. The heating table of the hot press was first set to 190°C for preheating for 30 minutes. The stacked fiber felts were placed in the mold and kept at 5 MPa for 10 minutes, and then the pressure was released for 5 minutes to expel the air. Then, the pressure was applied at 200°C and 210°C for 10 minutes and then released for 5 minutes. Finally, a pressure of 7.5 MPa was applied at 220°C for 1 hour, and a three-dimensional woven structure composite film with a polyetherimide volume fraction of 5% was obtained after cooling by air blowing.
[0043] Implementation Case 4:
[0044] (1) Weigh 3.5 g of polyvinylidene fluoride-hexafluoropropylene powder and place it in a 50 mL beaker. Add 8 mL of N-methylpyrrolidone solvent and 8 mL of acetone into the beaker and stir at room temperature for 24 h to obtain an outer layer precursor solution.
[0045] (2) Weigh 2.3 g of polyetherimide particles and place them in a 50 mL beaker. Add 9 mL of N-methylpyrrolidone solvent and 8 mL of acetone into the beaker and stir at 40 °C for 12 h to obtain an inner layer precursor solution.
[0046] (3) Use two 10mL syringes to absorb the inner and outer layer precursor solutions respectively, connect the two syringes to the two interfaces of the 22G / 17G coaxial spinning needle respectively, apply a high voltage of 17kV for the electrospinning process, the speed of the spinning receiving shaft is 580 rpm, the propulsion speeds of the inner and outer layer solutions are 1 μL / min and 9 μL / min respectively, the ambient temperature of the entire electrospinning process is maintained at 26°C, the humidity is less than 15% RH, and the spinning time is 18h.
[0047] (4) The prepared fiber felt was removed from the aluminum foil, first dried in air at 120°C for 2 h to remove excess solvent, and then dried in a vacuum for 24 h.
[0048] (5) Stack two layers of fiber mat in the same direction and place them in a mold. First, set the heating table of the hot press to 190°C for preheating for 30 minutes. Put the stacked fiber mat in and keep it at 5MPa for 10 minutes, then release the pressure for 5 minutes to expel the air. Then, pressurize at 200°C and 210°C for 10 minutes and then release the pressure for 5 minutes. Finally, apply a pressure of 7.5MPa at 220°C for 1 hour, and after cooling with air, obtain a single-direction structure composite film with a polyetherimide volume fraction of 8%.
[0049] Implementation Case 5:
[0050] (1) Weigh 3.5 g of polyvinylidene fluoride-hexafluoropropylene powder and place it in a 50 mL beaker. Add 8 mL of N-methylpyrrolidone solvent and 8 mL of acetone into the beaker and stir at room temperature for 24 h to obtain an outer layer precursor solution.
[0051] (2) Weigh 2.3 g of polyetherimide particles and place them in a 50 mL beaker. Add 9 mL of N-methylpyrrolidone solvent and 8 mL of acetone into the beaker and stir at 40 °C for 12 h to obtain an inner layer precursor solution.
[0052] (3) Use two 10 mL syringes to absorb the inner and outer layer precursor solutions respectively, connect the two syringes to the two interfaces of the 22G / 17G coaxial spinning needle respectively, apply a high voltage of 17 kV for the electrospinning process, the speed of the spinning receiving shaft is 560 rpm, the propulsion speeds of the inner and outer layer solutions are 1 μL / min and 9 μL / min respectively, the ambient temperature of the entire electrospinning process is maintained at 26°C, the humidity is less than 15% RH, and the spinning time is 18 h.
[0053] (4) The prepared fiber felt was removed from the aluminum foil, first dried in air at 120°C for 2 h to remove excess solvent, and then dried in a vacuum for 24 h.
[0054] (5) Stack two layers of fiber mat in a cross-vertical direction and place them in a mold. First, set the heating table of the hot press to 190°C for preheating for 30 minutes. Place the stacked fiber mat in the mold and keep it at 5MPa for 10 minutes, then release the pressure for 5 minutes to expel the air. Then, pressurize at 200°C and 210°C for 10 minutes and then release the pressure for 5 minutes. Finally, apply a pressure of 7.5MPa at 220°C for 1 hour, and after cooling with air, obtain a double-layer cross-structure composite film with a polyetherimide volume fraction of 8%.
[0055] Implementation Case 6:
[0056] (1) Weigh 3.5 g of polyvinylidene fluoride-hexafluoropropylene powder and place it in a 50 mL beaker. Add 8 mL of N-methylpyrrolidone solvent and 8 mL of acetone into the beaker and stir at room temperature for 24 h to obtain an outer layer precursor solution.
[0057] (2) Weigh 2.3 g of polyetherimide particles and place them in a 50 mL beaker. Add 9 mL of N-methylpyrrolidone solvent and 8 mL of acetone into the beaker and stir at 40 °C for 12 h to obtain an inner layer precursor solution.
[0058] (3) Use two 10mL syringes to absorb the inner and outer layer precursor solutions respectively, connect the two syringes to the two interfaces of the 22G / 17G coaxial spinning needle respectively, apply a high voltage of 17kV for the electrospinning process, the speed of the spinning receiving shaft is 600 rpm, the propulsion speeds of the inner and outer layer solutions are 1 μl / min and 9 μl / min respectively, the ambient temperature of the entire electrospinning process is maintained at 26°C, the humidity is less than 20% RH, and the spinning time is 13h.
[0059] (4) The prepared fiber felt was removed from the aluminum foil, first dried in air at 120°C for 2 h to remove excess solvent, and then dried in a vacuum for 24 h.
[0060] (5) The fiber felts were stacked in three layers in a cross-vertical direction and placed in a mold. The heating table of the hot press was first set to 190°C for preheating for 30 minutes. The stacked fiber felts were placed in the mold and kept at 5 MPa for 10 minutes, and then the pressure was released for 5 minutes to expel the air. Then, the pressure was applied at 200°C and 210°C for 10 minutes and then released for 5 minutes. Finally, a pressure of 7.5 MPa was applied at 220°C for 1 hour, and a three-dimensional woven structure composite film with a polyetherimide volume fraction of 8% was obtained after cooling by air blowing.
[0061] Implementation Case 7:
[0062] (1) Weigh 3.6 g of polyvinylidene fluoride-hexafluoropropylene powder and place it in a 50 mL beaker. Add 8 mL of N-methylpyrrolidone solvent and 8 mL of acetone to the beaker and stir at room temperature for 24 h to obtain an outer layer precursor solution.
[0063] (2) Weigh 3.15 g of polyetherimide particles and place them in a 50 mL beaker. Add 9 mL of N-methylpyrrolidone solvent and 8 mL of acetone into the beaker and stir at 40 °C for 12 h to obtain an inner layer precursor solution.
[0064] (3) Use two 10mL syringes to absorb the inner and outer layer precursor solutions respectively, connect the two syringes to the two interfaces of the 22G / 17G coaxial spinning needle respectively, apply a high voltage of 16.7kV to carry out the electrospinning process, the speed of the spinning receiving shaft is 620 rpm, the propulsion speeds of the inner and outer layer solutions are 1 μL / min and 9 μL / min respectively, the ambient temperature of the entire electrospinning process is maintained at 26°C, the humidity is less than 30% RH, and the spinning time is 17h.
[0065] (4) The prepared fiber felt was removed from the aluminum foil, first dried in air at 120°C for 2 h to remove excess solvent, and then dried in a vacuum for 24 h.
[0066] (5) Stack two layers of fiber mat in the same direction and place them in a mold. First, set the heating table of the hot press to 190°C for preheating for 30 minutes. Place the stacked fiber mat in the mold and keep it at 5 MPa for 10 minutes, then release the pressure for 5 minutes to expel the air. Then, pressurize at 200°C and 210°C for 10 minutes and then release the pressure for 5 minutes. Finally, apply a pressure of 7.5 MPa at 220°C for 1 hour, and after cooling with air, obtain a single-direction structure composite film with a polyetherimide volume fraction of 10%.
[0067] Implementation Case 8:
[0068] (1) Weigh 3.6 g of polyvinylidene fluoride-hexafluoropropylene powder and place it in a 50 mL beaker. Add 8 mL of N-methylpyrrolidone solvent and 8 mL of acetone to the beaker and stir at room temperature for 24 h to obtain an outer layer precursor solution.
[0069] (2) Weigh 3.15 g of polyetherimide particles and place them in a 50 mL beaker. Add 9 mL of N-methylpyrrolidone solvent and 8 mL of acetone into the beaker and stir at 40 °C for 12 h to obtain an inner layer precursor solution.
[0070] (3) Use two 10mL syringes to absorb the inner and outer layer precursor solutions respectively, connect the two syringes to the two interfaces of the 22G / 17G coaxial spinning needle respectively, apply a high voltage of 16kV for the electrospinning process, the speed of the spinning receiving shaft is 650 rpm, the propulsion speeds of the inner and outer layer solutions are 1 μl / min and 9 μl / min respectively, the ambient temperature of the entire electrospinning process is maintained at 26°C, the humidity is less than 25% RH, and the spinning time is 15h.
[0071] (4) The prepared fiber felt was removed from the aluminum foil, first dried in air at 120°C for 2 h to remove excess solvent, and then dried in a vacuum for 24 h.
[0072] (5) Stack two layers of fiber mat in a cross-vertical direction and place them in a mold. First, set the heating table of the hot press to 190°C for preheating for 30 minutes. Place the stacked fiber mat in the mold and keep it at 5MPa for 10 minutes, then release the pressure for 5 minutes to expel the air. Then, pressurize at 200°C and 210°C for 10 minutes and then release the pressure for 5 minutes. Finally, apply a pressure of 7.5MPa at 220°C for 1 hour, and after cooling with air, obtain a double-layer cross-structure composite film with a polyetherimide volume fraction of 10%.
[0073] Implementation Case 9:
[0074] (1) Weigh 3.6 g of polyvinylidene fluoride-hexafluoropropylene powder and place it in a 50 mL beaker. Add 8 mL of N-methylpyrrolidone solvent and 8 mL of acetone to the beaker and stir at room temperature for 24 h to obtain an outer layer precursor solution.
[0075] (2) Weigh 3.15 g of polyetherimide particles and place them in a 50 mL beaker. Add 9 mL of N-methylpyrrolidone solvent and 8 mL of acetone into the beaker and stir at 40 °C for 12 h to obtain an inner layer precursor solution.
[0076] (3) Use two 10mL syringes to absorb the inner and outer layer precursor solutions respectively, connect the two syringes to the two interfaces of the 22G / 17G coaxial spinning needle respectively, apply a high voltage of 16kV for the electrospinning process, the speed of the spinning receiving shaft is 620 rpm, the propulsion speeds of the inner and outer layer solutions are 1 μL / min and 9 μL / min respectively, the ambient temperature of the entire electrospinning process is maintained at 26°C, the humidity is less than 20% RH, and the spinning time is 13h.
[0077] (4) The prepared fiber felt was removed from the aluminum foil, first dried in air at 120°C for 2 h to remove excess solvent, and then dried in a vacuum for 24 h.
[0078] (5) The fiber felts were stacked in three layers in a cross-vertical direction and placed in a mold. The heating table of the hot press was first set to 190°C for preheating for 30 minutes. The stacked fiber felts were placed in the mold and kept at 5 MPa for 10 minutes, and then the pressure was released for 5 minutes to expel the air. Then, the pressure was applied at 200°C and 210°C for 10 minutes and then released for 5 minutes. Finally, a pressure of 7.5 MPa was applied at 220°C for 1 hour, and a three-dimensional woven structure composite film with a polyetherimide volume fraction of 10% was obtained after cooling by air blowing.
[0079] Implementation Case 10:
[0080] (1) Weigh 3.6 g of polyvinylidene fluoride-hexafluoropropylene powder and place it in a 50 mL beaker. Add 8 mL of N-methylpyrrolidone solvent and 8 mL of acetone to the beaker and stir at room temperature for 24 h to obtain an outer layer precursor solution.
[0081] (2) Weigh 2.27 g of polyetherimide particles and place them in a 50 mL beaker. Add 9 mL of N-methylpyrrolidone solvent and 8 mL of acetone into the beaker and stir at 40 °C for 12 h to obtain an inner layer precursor solution.
[0082] (3) Use two 10mL syringes to absorb the inner and outer layer precursor solutions respectively, connect the two syringes to the two interfaces of the 21G / 17G coaxial spinning needle respectively, apply a high voltage of 17.4kV to carry out the electrospinning process, the speed of the spinning receiving shaft is 590 rpm, the propulsion speeds of the inner and outer layer solutions are 2 μL / min and 9 μL / min respectively, the ambient temperature of the entire electrospinning process is maintained at 26°C, the humidity is less than 10% RH, and the spinning time is 15h.
[0083] (4) The prepared fiber felt was removed from the aluminum foil, first dried in air at 120°C for 2 h to remove excess solvent, and then dried in a vacuum for 24 h.
[0084] (5) Stack two layers of fiber mat in the same direction and place them in a mold. First, set the heating table of the hot press to 190°C for preheating for 30 minutes. Place the stacked fiber mat in the mold and keep it at 5 MPa for 10 minutes, then release the pressure for 5 minutes to expel the air. Then, pressurize at 200°C and 210°C for 10 minutes and then release the pressure for 5 minutes. Finally, apply a pressure of 7.5 MPa at 220°C for 1 hour, and after cooling with air, obtain a single-direction structure composite film with a polyetherimide volume fraction of 15%.
[0085] Implementation Case 11:
[0086] (1) Weigh 3.6 g of polyvinylidene fluoride-hexafluoropropylene powder and place it in a 50 mL beaker. Add 8 mL of N-methylpyrrolidone solvent and 8 mL of acetone to the beaker and stir at room temperature for 24 h to obtain an outer layer precursor solution.
[0087] (2) Weigh 2.27 g of polyetherimide particles and place them in a 50 mL beaker. Add 9 mL of N-methylpyrrolidone solvent and 8 mL of acetone into the beaker and stir at 40 °C for 12 h to obtain an inner layer precursor solution.
[0088] (3) Use two 10mL syringes to absorb the inner and outer layer precursor solutions respectively, connect the two syringes to the two interfaces of the 21G / 17G coaxial spinning needle respectively, apply a high voltage of 17.4kV to carry out the electrospinning process, the speed of the spinning receiving shaft is 600 rpm, the propulsion speeds of the inner and outer layer solutions are 2 μL / min and 9 μL / min respectively, the ambient temperature of the entire electrospinning process is maintained at 26°C, the humidity is less than 15% RH, and the spinning time is 13h.
[0089] (4) The prepared fiber felt was removed from the aluminum foil, first dried in air at 120°C for 2 h to remove excess solvent, and then dried in a vacuum for 24 h.
[0090] (5) Stack two layers of fiber mat in a cross-vertical direction and place them in a mold. First, set the heating table of the hot press to 190°C for preheating for 30 minutes. Place the stacked fiber mat in the mold and keep it at 5MPa for 10 minutes, then release the pressure for 5 minutes to expel the air. Then, pressurize at 200°C and 210°C for 10 minutes and then release the pressure for 5 minutes. Finally, apply a pressure of 7.5MPa at 220°C for 1 hour, and after cooling with air, obtain a double-layer cross-structure composite film with a polyetherimide volume fraction of 15%.
[0091] Implementation Case 12:
[0092] (1) Weigh 3.6 g of polyvinylidene fluoride-hexafluoropropylene powder and place it in a 50 mL beaker. Add 8 mL of N-methylpyrrolidone solvent and 8 mL of acetone to the beaker and stir at room temperature for 24 h to obtain an outer layer precursor solution.
[0093] (2) Weigh 2.27 g of polyetherimide particles and place them in a 50 mL beaker. Add 9 mL of N-methylpyrrolidone solvent and 8 mL of acetone into the beaker and stir at 40 °C for 12 h to obtain an inner layer precursor solution.
[0094] (3) Use two 10mL syringes to absorb the inner and outer layer precursor solutions respectively, connect the two syringes to the two interfaces of the 21G / 17G coaxial spinning needle respectively, apply a high voltage of 17kV for the electrospinning process, the speed of the spinning receiving shaft is 610 rpm, the propulsion speeds of the inner and outer layer solutions are 2 μL / min and 9 μL / min respectively, the ambient temperature of the entire electrospinning process is maintained at 26°C, the humidity is less than 10% RH, and the spinning time is 12h.
[0095] (4) The prepared fiber felt was removed from the aluminum foil, first dried in air at 120°C for 2 h to remove excess solvent, and then dried in a vacuum for 24 h.
[0096] (5) The fiber felts were stacked in three layers in a cross-vertical direction and placed in a mold. The heating table of the hot press was first set to 190°C for preheating for 30 minutes. The stacked fiber felts were placed in the mold and kept at 5 MPa for 10 minutes, and then the pressure was released for 5 minutes to expel the air. After that, the pressure was applied at 200°C and 210°C for 10 minutes and then released for 5 minutes. Finally, a pressure of 7.5 MPa was applied at 220°C for 1 hour, and after cooling by air, a three-dimensional woven structure composite film with a polyetherimide volume fraction of 15% was obtained.
[0097] The following is a comparison of the dielectric properties of the three-dimensional structure designed by the present invention with other structures of the same volume fraction:
[0098] Table 1
[0099] Breakdown field strength 5% sample 8% sample 10% sample 15% sample Single direction 621.5kV / mm 663.7kV / mm 691.4kV / mm 628.8kV / mm Double cross 638.6kV / mm 687.1kV / mm 695.8kV / mm 636.2kV / mm Three-dimensional weaving 653.4kV / mm 699.7kV / mm 737.5kV / mm 687.0kV / mm
[0100] The Weibull distribution of the breakdown voltage of the 10% three-dimensional woven composite film is as follows: Figure 3 As shown;
[0101] Table 2
[0102] Energy storage density 5% sample 8% sample 10% sample 15% sample Single direction <![CDATA[15.9J / cm 3 ]]> <![CDATA[21.5J / cm 3 ]]> <![CDATA[19.1J / cm 3 ]]> <![CDATA[17.8J / cm 3 ]]> Double cross <![CDATA[18.3J / cm 3 ]]> <![CDATA[23.8J / cm 3 ]]> <![CDATA[22.5J / cm 3 ]]> <![CDATA[19.9J / cm 3 ]]> Three-dimensional weaving <![CDATA[18.5J / cm 3 ]]> <![CDATA[24.9J / cm 3 ]]> <![CDATA[29.3J / cm 3 ]]> <![CDATA[20.9J / cm 3 ]]>
[0103] The discharge energy density of 10% three-dimensional woven structure composite film under different electric fields is as follows Figure 4 As shown;
[0104] Table 3
[0105]
[0106]
[0107] The charge and discharge efficiency of 10% three-dimensional woven structure composite film under different electric fields is as follows Figure 5 As shown;
[0108] Comparison of the maximum discharge energy density and breakdown strength of three composite films with different structures Figure 6 shown.
Claims
1. A method for preparing a fiber braided structure dielectric film for a high energy storage density capacitor, characterized in that: A polyetherimide / polyvinylidene fluoride-hexafluoropropylene composite film with a three-dimensional cross-woven structure is prepared by electrospinning and hot pressing, and the steps are as follows: Step 1: Weigh a certain mass of polyvinylidene fluoride-hexafluoropropylene powder and place it in a beaker, add N-methylpyrrolidone solvent and acetone in a volume ratio of 1:1 into the beaker, and stir at room temperature to obtain an outer layer precursor solution; Step 2: Weigh a certain mass of polyetherimide particles and place them in a beaker, add N-methylpyrrolidone solvent and acetone in a volume ratio of 9:8 into the beaker, and stir at 40° C. to obtain an inner layer precursor solution; Step 3: Use two 10mL syringes to absorb the inner and outer layer precursor solutions respectively, connect the two syringes to the two interfaces of the special coaxial spinning needle respectively, apply a high voltage of 16-18kV for the electrospinning process, and the speed of the spinning receiving shaft is 600+50 or 600-50 rpm. The propulsion speed ratio of the inner and outer layer solutions is consistent with the ratio of the inner and outer layer areas of the coaxial spinning needle; Step 4: remove the prepared fiber felt from the aluminum foil and dry it; Step 5: Place the fiber felt in the mold, set the heating table of the hot press to 190℃ and preheat for 30 minutes, put the stacked fiber felt in, keep it at 5MPa for 10 minutes, and then release the pressure for 5 minutes to expel the air; Then, the film was pressurized at 200°C and 210°C for 10 min and then released for 5 min. Finally, a pressure of 7.5 MPa was applied at 220°C for 1 h, and composite films with different structures were obtained after cooling with air.
2. The method for preparing a fiber braided structure dielectric film for a high energy storage density capacitor according to claim 1, characterized in that: In step 1, the mass of polyvinylidene fluoride-hexafluoropropylene powder is adjusted to obtain outer layer precursor solutions with different volume fractions.
3. The method for preparing a fiber braided structure dielectric film for a high energy storage density capacitor according to claim 1, characterized in that: In step 2, the mass of the polyetherimide particles is adjusted to obtain inner layer precursor solutions with different volume fractions.
4. The method for preparing a fiber braided structure dielectric film for a high energy storage density capacitor according to claim 1, characterized in that: In step 3, the product of the ratio of the volume concentration of polyetherimide in the inner layer precursor solution to the volume concentration of polyvinylidene fluoride-hexafluoropropylene in the outer layer precursor solution and the ratio of the inner and outer layer areas of the coaxial spinning needle is the volume ratio of the two components of polyetherimide and polyvinylidene fluoride-hexafluoropropylene in the obtained spun fiber, that is, 5. The method for preparing a fiber braided structure dielectric film for a high energy storage density capacitor according to claim 1 or 4, characterized in that: In step 3, the ambient temperature of the entire electrospinning process is maintained at 26° C., the humidity is between 10% RH and 30% RH, and the spinning time is 12 h to 18 h.
6. The method for preparing a fiber braided structure dielectric film for a high energy storage density capacitor according to claim 1, characterized in that: In step 4, the excess solvent is first removed by drying in air at 120° C. for 2 h, and then drying in vacuum for more than 24 h.
7. The method for preparing a fiber braided structure dielectric film for a high energy storage density capacitor according to claim 1, characterized in that: In step 5, the fiber mat is placed in a mold in 2 to 3 layers in the same direction or in a cross-vertical direction.
8. A fiber braided structure dielectric film for high energy storage density capacitors, characterized in that: The method is prepared by any one of claims 1 to 7.
Citation Information
Patent Citations
Battery diaphragm and preparation method thereof
CN115954610A
Preparation method of high-breakdown-strength dielectric film for high-energy-storage-density capacitor
CN117174487A
Composite film and preparation method and application thereof
CN119081402A
Nanofibre lithium-ion battery separator with composite structure and preparation method therefor
WO2013159752A1